Gangguan Haid Pada Wanita Dengan Sindrom Ovarium Polikistik (PCOS) - Rusmiati; Hasnah; Risnahyanti; Nur Indah; Sevina Az; Meike Saputri; Chantika (2026)
Polycystic Ovary Syndrome (PCOS) is a complex endocrine disorder that often affects women of reproductive age and can cause various types of menstrual disorders, such as polymenorrhea, oligomenorrhea, amenorrhea, menorrhagia, metroragia and hypomenorrhea to irregular cycles. These disorders are generally caused by hormonal imbalances, such as increased androgens, abnormal LH/FSH ratio and insulin resistance. Risk factors that aggravate the condition include obesity, unhealthy lifestyle, stress, insulin resistance and genetic factors. The impact is not only on the reproductive system such as infertility, but also psychological risks and long-term complications such as metabolic syndrome and endometrial cancer. PCOS treatment includes lifestyle changes, hormonal therapy, as well as additional medications such as metformin. An in-depth understanding of the relationship between PCOS and menstrual disorders is important for early intervention to prevent long-term complications and improve the quality of life of women with PCOS.